A study of ecological sanitation as a way to combat urban water stress - Mah, Darrien Yau Seng; Frederik, Josep Putuhena, Prof. Dr.; Salim, Said, Prof. Dr.; Law, Puong Ling, Dr. (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/